Attributes Influencing Brand Loyalty: A Study of Products, Services, and Purchases - Djaelani Susanto; Kifni Yudianto; Arif Fakhrudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The quality of goods and service is determined by the customers. Therefore, customer satisfaction can be achieved bu giving a good quality. Providing customer satisfaction, measuring it and identifying the factors contributing the customer satisfaction is necessary. In conventional marketing, many marketers believe that the customers loyalty upon a product depends on the customers satisfaction. During the time, the marketers recognize that customer loyalty is the drine to make purchase. This study tests the effect from attribute related to the product, attribute related to the service, attribute related to the purchase towards the brand loyalty on Rent cars Murni. The independent variable involves attribute related to the product, attribute related to the service, attribute related to the purchase. The dependent variable in this study is the brand loyalty. The result of the ANOVA test on the F-test shows that there is significant effect from attribute related to the product, attribute related to the service, attribute related to the purchase towards the brand loyalty on Murni car rental.